Experimental Evaluation of the Hybrid-Bifacial Cooling of a PV Panel in Arid Weather Using Channel Heat Exchanger and Impingement Flow Nozzles - Ali Balal; Ghanbar Ali Sheikhzadeh; Abolfazl Fattahi (Journal of Heat and Mass Transfer Research)
In the current global energy conditions, with a growing concern for carbon emissions, the adoption of renewable energy sources is on the rise. Solar panels have emerged as a highly promising method for electrical-thermal energy generation and are widely employed in both industrial and residential settings. This study focuses on evaluating the impact of cooling on PV panel systems and its effect on electrical and thermal efficiency. A hybrid method utilizing both air and water on the PV panels is examined, and the results are compared to those of a reference panel. The experiments were conducted in Kashan, Iran, located at coordinates 34°06' N 51°23' E, in July 2023. By implementing the proposed cooling method, significant improvements in the maximum daily electrical, thermal, and total efficiencies can be achieved, surpassing 20%, 30%, and 50%, respectively. The findings indicate that cooling with water proves more advantageous in terms of thermal energy generation, although it slightly decreases the coefficient of energy due to the additional energy required for water pumping compared to air blowing. Furthermore, the study reveals that bifacial cooling, employing jets to cool both sides of the PV panel, significantly enhances thermal and electrical efficiency, particularly in hot and dry weather conditions.